PathSTORM: a road to early cancer detection. (2nd September 2020) - Troy, Kris; Liu, Yang; Hainer, Sarah J.
ABSTRACT: Disruption of chromatin structure could enable early carcinogenesis by facilitating malignant transformation. Using stochastic optical reconstruction microscopy optimized for pathological tissue (PathSTORM), we uncovered a gradual decompaction of higher-order chromatin folding through progressive stages of carcinogenesis. We demonstrated potential detection of pre-cancerous genomic architecture not easily discernible by conventional pathology.